2006
DOI: 10.1037/0021-843x.115.4.787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on the overlap between low IQ and antisocial behavior in young children.

Abstract: The well-documented relation between the phenotypes of low IQ and childhood antisocial behavior could be explained by either common genetic influences or environmental influences. These competing explanations were examined through use of the Environmental Risk Longitudinal Twin Study 1994-1995 cohort (Moffitt & the E-Risk Study Team, 2002) of 1,116 twin pairs and their families. Children's IQ was assessed via individual testing at age 5 years. Mothers and teachers reported on children's antisocial behavior at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 51 publications
6
41
1
1
Order By: Relevance
“…(2) To what extent does the environment modify the neural blueprint? In typically developing populations, the concept of gene-environment interactions for cognitive development is well accepted [Kim-Cohen et al, 2004;Caspi and Moffitt, 2006;Koenen et al, 2006;Rutter et al, 2006]. Very little research in mental retardation/developmentally delayed populations, however, and few in VCFS, have addressed this question.…”
Section: Future Research Directionsmentioning
confidence: 98%
“…(2) To what extent does the environment modify the neural blueprint? In typically developing populations, the concept of gene-environment interactions for cognitive development is well accepted [Kim-Cohen et al, 2004;Caspi and Moffitt, 2006;Koenen et al, 2006;Rutter et al, 2006]. Very little research in mental retardation/developmentally delayed populations, however, and few in VCFS, have addressed this question.…”
Section: Future Research Directionsmentioning
confidence: 98%
“…Some research found that children with conduct disorders scored about eight IQ points lower than their non-disordered counterparts on intelligence tests, scoring particularly lower on the verbal scale (Lynam et al 1993;Prentice and Kelly 1963). Low IQ scores obtained at age 5 also have been related to antisocial behavior scores at age 7 (Koenen et al 2006). The relationship between intellectual deficits and the developmental progression of antisocial behaviors in childhood, adolescence, and adulthood have been well supported by research.…”
Section: Introductionmentioning
confidence: 94%
“…Some other studies discussed ASPD from neuropsychological point of view, they concluded that ASPD individuals tend to suffer from cognitive and behavioral problems due to tampered function in DLPFC and VMPFC area of the brain (Dolan & Park, 2002). In another study conducted by Karestan and Koenen (2008), they studied Genetic Influences on the Overlap between Low IQ and Antisocial Behavior in Young Children; they concluded that Low IQ was associated with antisocial behavior at age 5 years and anticipated comparatively higher antisocial behavior scores at age 7 years when antisocial behavior at age 5 years was controlled. This link was dramatically boosted among boys than among girls.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic influences mutual to both phenotypes explained 100% of the low IQantisocial behavior relation in boys. Findings suggest that specific candidate genes and neurobiological processes should be tested in relation to both phenotypes (Karestan, Koenen, Terrie, Fruhling, & Alan, 2008). As we can see various clinicians and scientists have assessed various aspects of ASPD individuals function, but current study stands out, because it meticulously assess EM and EI subtypes of these individuals.…”
Section: Discussionmentioning
confidence: 99%